Comparison of the femur proximal extremity's densitometric values in young and healthy study participants: left-handed vs. right-handed. - S., Naranjo-Kalinowska; Santana P., Saavedra; F., De la Rosa-Fernández; N., Suárez-Ramírez; Romero M. J., Gómez de Tejada; Henríquez M., Sosa (Journal of Osteoporosis & Mineral Metabolism / Revista de Osteoporosis y Metabolismo Mineral (Spanish edition))
Objetive: Physical activity is a key factor for bone mineral density. Left-handed people exercise more left limbs than right-handed do. The objective of this study was to determine whether left-handed participants have higher values of BMD in the left lower limbs (proximal femur) and right-handed subjects have them higher in the right lower ones. Material and methods: Cross-sectional observational study performed on young and healthy men and women who do not practice any sport activity, and who were divided into two groups according to their laterality, established by the Edinburgh Handedness Inventory. The bone mineral density in the lumbar spine and the proximal extremity of both femurs was measured in all of the participants using a Hologic QDR 4500 Discovery® densitometer. Results: From the 122 study participants, 62 were right-handed and 60 were left-handed. Statistically significant differences were not perceived among the participants, nor age-related, or in male-female proportion, body mass index or according to the subjects' lifestyle: alcohol consumption, tobacco use and physical activity practiced during leisure time. Left and right-handed participants showed similar values for bone mineral density in the spine and in all the anatomical regions measured (femoral neck, total hip, trochanter and intertrochanter) in the right and left femurs. However, lower BMD values were obtained in all the measured locations of the left femur, compared to the same measurements in the right femur (these differences being statistically significant) when considered all the participants as a whole or when grouping them according to their laterality. Conclusions: Differences of BMD in the measured locations of both right and left-handed participants were not observed. However, the BMD values in the left side were significantly lower in all subjects, regardless of their laterality.